2016
DOI: 10.1111/bcpt.12640
|View full text |Cite
|
Sign up to set email alerts
|

Concentration–Response Relationship of Hearing Impairment Caused by Quinine and Salicylate: Pharmacological Similarities but Different Molecular Mechanisms

Abstract: This review has the purpose to summarize concentration-effect studies made with quinine and to compare the effects on hearing between quinine and salicylate. Quinine and salicylate have roles in experimental hearing research and may induce pronounced and reversible hearing impairment when administered in sizeable doses. The quinine-induced increase in hearing threshold and its recovery can be analysed according to 'the psychophysical power function'. The power function is a special case of the Hill equation wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Salicylates rapidly enter the cochlea and diffuse all parts of the cochlear duct. In animals, serum salicylate levels correlated with perilymph salicylate concentrations and hearing loss . In addition, they suppressed cochlear function preferentially at high and low frequencies and enhanced the neural activity in the auditory thalamus, cortex, and amygdala .…”
Section: Selected Ototoxic Drugsmentioning
confidence: 92%
See 1 more Smart Citation
“…Salicylates rapidly enter the cochlea and diffuse all parts of the cochlear duct. In animals, serum salicylate levels correlated with perilymph salicylate concentrations and hearing loss . In addition, they suppressed cochlear function preferentially at high and low frequencies and enhanced the neural activity in the auditory thalamus, cortex, and amygdala .…”
Section: Selected Ototoxic Drugsmentioning
confidence: 92%
“…This increase is dose dependent and already occurs at therapeutic doses in the high frequency range. Thus, to avoid an increase in ototoxicity, co‐administration of quinine with other ototoxic drugs should be avoided …”
Section: Selected Ototoxic Drugsmentioning
confidence: 99%
“…QN also induced tinnitus in the behavioral model of tinnitus in rats (41); however, in another study animals treated with 200 mg/kg/d QN did not exhibit tinnitus-like behavior when assessed using the gap prepulse inhibition of acoustic startle (42). Interestingly, quinoline drugs have been found to prevent ototoxicity by loop diuretics (furosemide/ethacrynic acid), aminoglycosides, and cisplatin in animal models based on chinchilla and zebrafish (20,(43)(44)(45). QN derivatives reduce uptake of gentamicin, neomycin, and cisplatin into hair cells (44,45).…”
Section: Mechanisms Of Ototoxicitymentioning
confidence: 99%
“…Quinine can negatively affect the auditory system at the level of the central auditory pathway and the auditory periphery. Several hypotheses about changes in cochlea have also been proposed, such as impairment of outer hair cells (OHCs), reduction in the blood flow, and microangiopathy due to quinine-induced thrombocytopenia and disseminated intravascular coagulation (19)(20)(21).…”
Section: Mechanisms Of Ototoxicitymentioning
confidence: 99%
“…In addition to its blocking effect on prestin, salicylate may affect the mechanical properties of the stereocilia bundle by decreasing its bending stiffness (8). Accordingly, several studies have demonstrated decreased OHC motility with high-dose aspirin intake, which may result in hearing loss (9,10). Salicylate administration may cause tinnitus in real life and some studies suggest that tinnitus may be considered an auditory nerve dysfunction (11).…”
Section: Introductionmentioning
confidence: 99%